Analisis Perlindungan Hukum terhadap Korban Tindak Pidana Perdagangan Organ untuk Kepentingan Transplantasi Organ Ginjal - Doni Hafendi; Gunardi Lie (Jurnal Hukum Lex Generalis, 2024)
Human organ trafficking, particularly involving kidneys, constitutes a grave crime that violates human rights and persists despite stringent national and international prohibitions. This crime is perpetrated not only by individuals but also by organized syndicates, including rogue state officials and transnational networks, exploiting societal vulnerabilities such as poverty, low education levels, and limited access to legal information. This study aims to thoroughly examine Indonesia's legal framework concerning human trafficking for kidney transplantation and evaluate the legal protections available to victims. Employing a normative juridical approach, the research analyzes relevant legislation, including the Eradication of Human Trafficking Law, the Health Law, and the Child Protection Law. Additionally, it reviews concrete cases and legal literature to depict real-world legal practices. The findings reveal that, despite existing regulations, legal protection for victims remains ineffective, particularly in terms of assistance, restitution, and rehabilitation. Many victims lack adequate access to justice, and perpetrators, including involved corporations, often escape proportionate legal consequences. The study also identifies normative and implementation challenges, with sanctions deemed insufficient to create a deterrent effect and inter-agency coordination remaining suboptimal.